2006
DOI: 10.2337/db06-0263
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue

Abstract: Adipose tissue, when carried around in excessive amounts, predisposes to a large number of diseases. Epidemiological data show that the prevalence of obesity has significantly increased over the past 20 years and continues to do so at an alarming rate. Here, some molecular aspects of the key constituent of adipose tissue, the adipocyte, are reviewed. While the adipocyte has been studied for many years and remarkable insights have been gained about some processes, many areas of the physiology of the fat cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
678
2
30

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 949 publications
(745 citation statements)
references
References 49 publications
18
678
2
30
Order By: Relevance
“…Genetic studies on single nucleotide polymorphisms of the adiponectin gene, as well as functional analyses, including transgenic or knockout mice suggested that reduced adiponectin levels play a causal role in the development of insulin resistance, metabolic syndrome, diabetes and atherosclerosis. [8][9][10][11] Moreover, human adiponectin mutation analysis 20 led to the identification of HMW adiponectin as the most active form. 21 We then developed an enzyme-linked immunosorbent assay system and showed that measurement of HMW is useful for the prediction of insulin resistance and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies on single nucleotide polymorphisms of the adiponectin gene, as well as functional analyses, including transgenic or knockout mice suggested that reduced adiponectin levels play a causal role in the development of insulin resistance, metabolic syndrome, diabetes and atherosclerosis. [8][9][10][11] Moreover, human adiponectin mutation analysis 20 led to the identification of HMW adiponectin as the most active form. 21 We then developed an enzyme-linked immunosorbent assay system and showed that measurement of HMW is useful for the prediction of insulin resistance and metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced adiponectin levels can also be caused by lifestyle changes causing obesity, such as a high-fat diet. Both functional [5][6][7] and genetic studies on adiponectin strongly suggest that reduced adiponectin levels play a causal role in the development of insulin resistance, metabolic syndrome, type 2 diabetes and atherosclerosis [8][9][10][11] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with increased risk of developing coronary heart disease, stroke, hypertension, type 2 diabetes, and dyslipidemia (Wannamethee et al, 2005;Pérez Pérez et al, 2007). Recently, low-grade inflammation has been considered as a possible new risk factor (Ridker, 2007) associated with obesity and visceral adiposity (Scherer, 2006). Traditional cardiovascular risk factors such as central obesity, high blood pressure, and insulin resistance, especially if components of the metabolic syndrome (MS) have been associated with increased levels of C-reactive protein (CRP), are a marker of low-grade inflammation that may have a major function in the pathogenesis of cardiovascular diseases (Ridker, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] These adipokines, which include leptin, adiponectin, tumor necrosis factor-a (TNFa), interleukin (IL)-6, visfatin and the recently described chemerin, act locally in an autocrine/paracrine manner and/or as endocrine signals to regulate appetite, energy expenditure and a range of other physiological processes such as insulin sensitivity, inflammation, angiogenesis and extracellular matrix remodeling. [8][9][10] In addition, as the largest energy reserve in the body, adipose tissue has a major impact on energy flux, plasma lipid levels and glucose uptake. A large body of evidence indicates that alterations in adipose tissue mass and metabolism have profound effects on whole body energy homeostasis.…”
Section: Introductionmentioning
confidence: 99%